Mobile-Assisted Language Learning Via WhatsApp Group: Interaction Patterns and Teacher Perspectives - Sari, Candrika Citra (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2024)
Mobile-Assisted Language Learning (MALL) is increasingly favored for its flexibility. This study analyzes interaction patterns in an L2 English training conducted entirely using WhatsApp group chat and examines the teacher’s perspective. Discourse analysis revealed a flexible Initiation-Response-Feedback (IRF) pattern, with students occasionally initiating turns. Emoticons and voice notes fostered emotional connections and mitigated direct feedback. The teacher found WhatsApp valuable for practicing all language skills, stressing the need for small group sizes. The study also noted discrepancies in adjacency pairs, which could be addressed using the direct reply feature to enhance conversational coherence and pedagogical effectiveness. Additionally, the study suggests combining the WhatsApp group chat with offline classes to increase students’ sense of responsibility and participation in the discussion.